Non-coding RNAs in lung cancer: emerging regulators of angiogenesis - Liao, Yajie; Wu, Xudong; Wu, Mengyu; Fang, Yuan; Li, Jie; Tang, Weiqiang (Journal of translational medicine, 2022)
Lung cancer is the second cancer and the leading cause of tumor-related mortality worldwide. Angiogenesis is a crucial hallmark of cancer development and a promising target in lung cancer. However, the anti-angiogenic drugs currently used in the clinic do not achieve long-term efficacy and are accompanied by severe adverse reactions. Therefore, the development of novel anti-angiogenic therapeutic approaches for lung cancer is urgently needed. Non-coding RNAs (ncRNAs) participate in multiple biological processes in cancers, including tumor angiogenesis. Many studies have demonstrated that ncRNAs play crucial roles in tumor angiogenesis. This review discusses the regulatory functions of different ncRNAs in lung cancer angiogenesis, focusing on the downstream targets and signaling pathways regulated by these ncRNAs. Additionally, given the recent trend towards utilizing ncRNAs as cancer therapeutics, we also discuss the tremendous potential applications of ncRNAs as biomarkers or novel anti-angiogenic tools in lung cancer.